Representative 2D-material-based nanocomposites and their emerging applications: a review. Issue 39 (7th July 2021) - Qadir, Akeel; Le, Top Khac; Malik, Muhammad; Amedome Min-Dianey, Kossi Aniya; Saeed, Imran; Yu, Yiting; Choi, Jeong Ryeol; Pham, Phuong V.
Abstract : Composites (or complex materials) are formed from two or many constituent materials with novel physical or chemical characteristics when integrated. Abstract : Composites (or complex materials) are formed from two or many constituent materials with novel physical or chemical characteristics when integrated. The individual components can be combined to create a unique composite material through mechanical transfer, physical stacking, exfoliation, derivative chemical mixtures, mixtures of solid solutions, or complex synthesis processes. The development of new composites based on emerging 2D nanomaterials has allowed for outstanding achievements with novel applications that were previously unknown. These new composite materials show massive potential in emerging applications due to their exceptional properties, such as being strong, light, cheap, and highly photodegradable, and their ability to be used for water splitting and energy storage compared to traditional materials. The blend of existing polymers and 2D materials with their nanocomposites has proven to be immediate solutions to energy and food scarcity in the world. Although much literature has been reported in the said context, we tried to provide an understanding about the relationship of their mechanisms and scope for future application in a comprehensive way. In this review, we briefly summarize the basic characteristics, novel physical and chemical behaviors, and new applications in the industry of the emerging 2D-material-based composites.